Assistance for the Preparation of Financial Statements and Taxes for MSMEs in Tegal City: Pendampingan Penyusunan Laporan Keuangan dan Pajak bagi UMKM Kota Tegal - Dewi Indriasih; Dien Noviany Rahmatika; Setyowati Subroto; Aminul Fajri; Jaka Waskito (Yayasan Ahmar Cendekia Indonesia, 2023)
One of the good economics of a country is supported by successful business management of MSMEs. Capital is the problem most often faced by business managers. MSME actors are still unable to get capital assistance even though the government has offered many credits through cooperation with banks. This is due to the inability of MSME managers to present precise, fast, accurate financial information and in accordance with generally accepted accounting standards (SAK – ETAP). In addition to these problems, MSME managers are also still unfamiliar with what is called taxation. The main problem related to the implementation of this community service is that it does not yet have the ability to prepare appropriate and accurate financial and tax information needed for business development. especially getting additional capital, while the market potential and production elements have been owned by MSMEs. The output achieved from this service activity is an increase in the understanding of MSME actors regarding the preparation of financial and tax reports for MSMEs. Abstrak Perekonomian suatu negara yang baik salah satunya ditunjang dari pengelolaan usaha pada UMKM yang berhasil. Permodalan merupakan permasalahan yang paling sering dihadapi oleh para pengelola usaha. Para pelaku UMKM masih belum bisa mendapatkan bantuan modal meskipun pemerintah sudah banyak menawarkan kredit melalui kerjasama dengan perbankan. Hal ini disebabkan oleh ketidakmampuan pengelola UMKM untuk menyajikan informasi keuangan yang tepat, cepat, akurat dan sesuai dengan standar akuntansi yang berlaku umum (SAK – ETAP). Selain masalah tersebut pengelola UMKM juga masih awam dengan yang namanya perpajakan. Permasalahan utama yang berkaitan dengan pelaksanaan pengabdian masyarakat ini adalah belum dimilikinya kemampuan untuk menyiapkan informasi keuangan dan perpajakan yang tepat, dan akurat yang diperlukan untuk pengembangan usaha, khususnya mendapatkan tambahan modal, sedangkan potensi pasar dan unsur produksi telah dimiliki oleh UMKM. Luaran yang dicapai dari kegiatan pengabdian ini adalah peningkatan pemahaman para pelaku UMKM mengenai penyusunan laporan keuangan dan pajak bagi UMKM.